PENGARUH PERLAKUAN AWAL PARTIKEL TERHADAP SERANGAN RAYAP TANAH PADA PAPAN PARTIKEL DARI LIMBAH BATANG KELAPA SAWIT (The Effect of Particle Pre-treatment of Subterranean Termite Attack on Particleboard from Oil Palm Trunks Waste) - Cut Yulia Maghfirah; Tito Sucipto; Rudi Hartono; Apri Heri Iswanto (Peronema Forestry Science Journal, 2014)
The utilization of oil palm trunk could be used as raw material for particleboard. It was not only increased the added value, but also used as substitution of wood. The purpose of this research evaluated the resistance of particleboard from waste of oil palm trunk on subterranean termites attack. The variation of particle pretreatment were dont by soaking the particle in hot water (1,2 and 3 hours) and in cold water (24, 48 and 72 hours.) Particleboard were made from oil palm trunk using isocyanate of 7%, with size 30 x 30 x 1 cm and density target of 0,70 gr/cm3. The evaluation of the samples were done by grave yard test along 100 days for resistance of particleboard on subterranean termites. The result showed that percentages of particleboard weight loss to subterranean termites were 19,99-63,92%. Based on subterranean termites attack, the particleboard made from oil palm trunk was classified as moderate to very destroy.Keywords: oil palm trunk, isocyanat, particle board, subterranean termites